Developing Critical Thinking: A Case Study of Teaching a Hemingway Story - Sharif, Mohd Yasmin (IIUC Studies, 2012)
English Literature is generally taught at tertiary level in Bangladesh to develop the critical and analytical ability of students, so as to enable them to develop their own evaluation and assessment of texts studied in classrooms. Such assumption often proves in vain, because even tertiary level students depend more on their cognitive capacity rather than their creative ability. Thus the ability of a student to think critically seldom grows because critical thinking (ct) is a faculty which only increases with practice and concentration. This paper endeavors to explore critical thinking ability as an important aspect of pedagogy which further enables a learner to be self-confident and inspirational in using his/her acquired knowledge both in the academy as well as in real life situations. The main focus of the paper is the traditional or classical process of literature study in classroom situations we usually practice in this part of the world to develop the psychology, thought process, and maturity of a learner. Literature is thought to have the power to develop or to create curiosity in learners in finding out the critical situation of real world. Again literature is believed to be a collection of characters, reflection of real life, absurdity, and the hundreds and thousands of problems and solutions to be encountered by a learner everyday which develops the faculty in learners to adjust or overcome hurdles in real life. Thus the paper through the analysis of a popular American short story A Clean, Well-Lighted Place by Ernest Hemingway tries to address the problems and solutions related to the teaching/development of critical thinking ability. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12255 IIUC Studies Vol.7 2011: 9-24